Exercise training to improve health related quality of life in long term survivors of major burn injury: A matched controlled study - Grisbrook, Tiffany; Reid, S.; Edgar, Dale; Wallman, K.; Wood, Fiona; Elliott, Catherine (Pergamon, 2012)
Objective: Patients often experience reduced health-related quality of life (HRQOL) following burn injury. Exercise training has been demonstrated to improve HRQOL in a number of clinical populations, yet it is unknown whether exercise can improve HRQOL in burns patients.Procedures: Nine burn-injured participants (42 18.38%TBSA: 6.56 3.68 years after injury) and 9 matched controls participated in a 12-week exercise programme. HRQOL was assessed via the Burn Specific Health Scale-Brief (BSHS-B) and the Medical Outcomes Study 36-Item Short Form (SF-36). Activity limitation was measured using the quick Disabilities of the Arm, Shoulder and Hand (QuickDASH).Results: The burns group had decreased HRQOL compared to the controls at baseline, as reported by the BSHS-B (t (16) = 3.51, p = 0.003) and some domains of the SF-36 including role physical (t (16) = 3.79, p = 0.002). Burned participants reported decreased activity levels compared to the controls as measured by the QuickDASH (t (16) = 2.19, p = 0.044). Exercise training improved SF-36 scores in both burn (t (8) = 3.77, p = 0.005) and control groups (t (8) = 2.71, p = 0.027). Following training there was no difference between the groups on the SF-36 or QuickDASH.Conclusion: Exercise training improves HRQOL and activity limitations in burn-injured patients to a level that is equivalent to that of their uninjured counterparts.